Perencanaan Keselamatan dan Kesehatan Kerja (K3) pada CV. Kurnia Agung Buayan dengan Metode Hazard And Operability Study (HAZOP) - Ramadhani, Widya Anggrianita; Hidayah, Muhammad Nur Wahyu (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to identify potential hazards, their sources, and the level of occupational accident risk in the tire retreading process at CV. Kurnia Agung Buayan using the Hazard and Operability Study (HAZOP) method. This method systematically identifies possible deviations in work activities and evaluates their impacts. Data were collected through observation, interviews, and documentation. The analysis found 13 potential work accidents categorized as 1 extreme, 4 high, 5 moderate, and 3 low risks. The main risks include accidents caused by machine fragments, cutter use without PPE, and direct contact with high-temperature machines. Recommended controls include the use of PPE, OHS training, preparation of standard operating procedures (SOPs), and improvements in workplace layout and conditions. The results are expected to serve as a reference for improving the company’s safety system, reducing accidents, and increasing employee productivity.